CRIME OF MONEY LAUNDERING AND MODUS BUSINESS LAW IN PERSPECTIVE - Lukmanul Hakim, Aal (DERECHTSSTAAT, 2015)
ABSTRACTÂ  Advance in science and technology today is an advancement of human civilizations that affect all aspects of life, include the growing and the diverting motifs and forms of crime increasingly. Along with the progress, the business area was not immune used as a means of committing a crime by the offender, one of them is money laundering that harness of advances in technology and the progress of the system that contained in the business area, such as the use of sophistication and to make ease of banking transactions, and other of business activity forms. Proportional to this, various efforts have been undertaken to prevent and to make the space narrower for the perpetrators of this money laundering, particularly by establishing a legal system in the business area that can eradicate the white -collar crime, both national and international research. Keywords: money laundering, modus, business law